2007
DOI: 10.1080/17470210701257685
|View full text |Cite
|
Sign up to set email alerts
|

Contingency judgements on the fly

Abstract: The present research was conducted to establish the validity of a novel procedure for measuring human contingency judgements aimed at shortening the length of conventional procedures. Cues and outcomes were simple geometric shapes that were presented in a rapid streaming fashion, reducing the length of a block of trials from several minutes to a few seconds. We establish the reliability of the procedure by replicating two central findings in the contingency judgement literature, and we elaborate on the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(85 citation statements)
references
References 19 publications
2
81
0
2
Order By: Relevance
“…Importantly, participants' responses on each trial can be objectively correct or incorrect (i.e., hits and false alarms). Crump, Hannah, Allan, and Hord (2007) have validated the streamed-trial method by replicating standard phenomena of contingency learning.…”
mentioning
confidence: 99%
“…Importantly, participants' responses on each trial can be objectively correct or incorrect (i.e., hits and false alarms). Crump, Hannah, Allan, and Hord (2007) have validated the streamed-trial method by replicating standard phenomena of contingency learning.…”
mentioning
confidence: 99%
“…The procedure elicits systematic biasing of contingency ratings by outcome frequency (Crump et al, 2007), and cue interaction effects as found in one-phase blocking and two-phase blocking ) tasks, including both forward and backward blocking.…”
Section: Signal Detection Theory and The Streamed-trial Proceduresmentioning
confidence: 99%
“…Crump's development of the streamed-trial procedure (Crump et al, 2007) performs such a transformation by presenting cue and outcome simultaneously and rapidly (100 ms). Figure 1 gives schematics for streamed trials in both single-cue (panel A) and one-phase blocking (panel B) paradigms.…”
Section: Signal Detection Theory and The Streamed-trial Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…At a given trial, the CS and the US can appear together, the CS can appear alone, the US can appear alone, or neither of them may be present. We call the frequencies of each of these possible combinations a, b, c, and d (see Table 1, e.g., Crump, Hannah, Allan, & Hord, 2007). Using the frequencies of each type of trial, the conditional probabilities of the US given the CS (p 1 ), and of the US given the absence of the CS (p 2 ), can be calculated.…”
Section: Introductionmentioning
confidence: 99%